Literasi Digital UMKM Agribisnis dalam Adopsi Strategi Pemasaran Digital di Kecamatan LimbotoKabupaten Gorontalo - Iman, Mohamad Rizky; Bakari, Yuliana; Moonti, Agustinus (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2024)
This research is aimed at analyzing:“How the influence of digital literacy on the tendency of entrepreneurs to secure limboto in adopting digital marketing”. The research was carried out for four months from the start of preparation to the preparation. The type of research used is the type of explanatory with a quantitative approach. The data collection technique is done using a questionnaire (angket). Research instrument testing using instrument testing, and classical assumption testing. The data analysis technique used is a double linear regression analysis analyzed using spss 21. The results of this survey showed below: Technological readiness variables have a significant influence on entrepreneurs' tendencies to adopt digital marketing and digital literacy variables negatively affect entrepreneur's tendencies in dealing with digital marketing.